BAURAN PEMASARAN KRIPIK DI UD CITRA SNACK PRIGEN PASURUAN - Farah Mutiara; A Yusuf Kholil (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2021)
There are various types of chips produced by UD. CITRA SNACK, namely jackfruit chips, honey potato chips and purple sweet potato chips. The purpose of this study was to determine the Marketing Strategy for Chips at UD Citra Snack Prigen Pasuruan. The qualitative descriptive analysis method is used to answer the first objective, namely to analyze the marketing mix strategy of the UD Citra Snack agroindustry, namely by using the 4P variables consisting of: product, price, place and promotion. ).Product Development Results UD CITRA SNACK always strives to provide quality quality products which is guaranteed. The price set by UD. CITRA SNACK above competitors' prices. The pricing is because the quality and service of the chips provided by the company are superior to competitors. Efforts made by UD. CITRA SNACK to increase its market share in the midst of competitive competition by means of promotion. Several forms of promotion by UD. CITRA SNACK include: advertising, which is a form of promotion carried out both through print and electronic media, by selecting the best media as a means to advertise products